Principles of Education According to the Al-Qur'an - Umar Dalimunthe; Kadar; Alwizar (Global Action and Education for Society, 2026)
This article examines the principles of education from the perspective of the Qur'an as the main foundation in forming knowledgeable, moral, and responsible human beings. Education in Islam includes not only intellectual aspects, but also spiritual and moral aspects, as reflected in key terms such as al-tarbiyah, al-ta'lim, al-ta'dib, al-tadris, and al-tazkiyah. Each of these terms describes a comprehensive and holistic approach to education. In addition, this article explains various principles of education based on the Qur'an, including: the principle of divinity, the obligation to learn and teach, lifelong education, integration and balance, respect for individual differences, openness and professionalism, and the importance of research and planning. All of these principles aim to create an education system that not only develops knowledge, but also fosters character and brings humans closer to Allah SWT.